Modelling, simulation and experimental verification of a wheeled-locomotion system based on omnidirectional wheels - Flores Álvarez, Pedro Alonso (2016)
The following work focuses on the kinematic and dynamic study of a four-wheeled robot, which is equipped with omnidirectional Mecanum wheels. The main objective of the thesis is to obtain a mathematical model from which both the kinematics and kinetics of the robot can be analyzed. Furthermore, the study presents a methodology to optimize the torques (and subsequent associated voltages) provided by each of the motors on the robot for a given trajectory. A system in which a non-powered trailer pulled by the robot is also analyzed at a kinematic level. In this stage, four different cases are considered. The construction of the trailer is also described on this work. In the first chapter, the global state of the art on analysis and control of omnidirectional robots (with focus on robots with Mecanum wheels) is presented. In the second chapter, the physical considerations for the general movement of the robot are analyzed, in order to derive the kinematic constrain equations of the locomotion system. The differential equation of motion is then derived using Lagrange-equations with multipliers. This chapter presents as well the kinematic analysis for a robot-trailer system. The third chapter describes the general process on the design of the trailer, including the rejected ideas for its construction. The fourth chapter focuses on verifying the final results of the design process, as well as tests to check the mobility of the system. Conclusions and future work are analyzed on the final part of the document, as well as the references and the acknowledgments to all the people involved in the project.